Решение татарского вопроса в процессе формирования и деятельности системы местных советов Автономной Крымской ССР в 1920-е гг. - Пащеня, В.Н. (Культура народов Причерноморья, 2006)
The solution of the problem of socialist-political development of the Crimean Tatar nation which was illegally deported by Stalin,s regime from its motherland in 1944 is now an essentially important element of the modern administrative management in the Crimean Autonomous Republic of the XXI century. In Ukraine this problem is solved by the State Committee of the National and Immigrant Affairs and in Crimean - by the Republican Committee and the Soviet of Representatives of the Crimean Tatar Nation at the President,s Office and by other structures as well. The successful solution of this problem can only be based on the objective research of this experience gained in Crimea in the 1920s when right after the end of the Civil war the process of raising of national confidence and cultural recognition of the whole 59 nations which inhabited the peninsula in that period especially concerning the Tatars.This article is aimed on the complex solution of the Tatar problem in the process of organization and activity. Важнейшим элементом современного этапа управленческого менеджмента в Автономной Республике Крым начала XXI в. является решение проблемы социально-политического развития крымскотатарского народа, незаконно депортированного сталинским режимом со своей этнической родины в 1944 году. Задачу эту в Украине решает Государственный комитет по делам национальностей и эмиграции, в Крыму- Республиканский комитет, а также Совет представителей крымскотатарского народа при Президенте Украины и другие структуры. Успешное решение этой проблемы возможно на базе объективного исследования того опыта, который был накоплен в Крыму в 1920-е гг., когда после завершения Гражданской войны здесь начался процесс подъема национальных культур и самосознания всех 59 народов, населяющих полуостров в то время, прежде всего татарского. Целью данной статьи является комплексный анализ решения татарского вопроса в процессе формирования и деятельности системы местных советов Крымской автономии как полномочных органов новой власти на местах в 1920-е гг.